Race, equity, and public schools in post-apartheid South Africa: equal opportunity for all kids? - Yamauchi, Futoshi (Elsevier, 2005)
This paper examines dynamic changes in educational quality and equity differences between Black and other population groups in post-Apartheid South African public schools, using the ratio of learners to educators in each school, available from the School Register of Needs, 1996 and 2000. The analysis incorporates school or community-level unobservables and the endogenous movement of learners. This paper shows that (i) the learner–educator ratios significantly differ between formerly Black and White primary and secondary schools in 1996 and 2000, and (ii) in the dynamic adjustment of educators in response to changes in learner size in this period, there are significant differences between formely Black and non-Black (White, Coloured and Indian) primary schools. The opportunities for education quality in public schools are still unequal between Black and White children even after the abolition of Apartheid, and given that school quality affects returns to schooling and earnings opportunities in labour markets, the inequality causes income inequality between Black and White. Our empirical result calls for stronger policy intervention to support Black schools and children in South Africa.